New haplotypes of AvrPi-54 gene detected in Pyricularia oryzae from Malaysia, India and China - Elissa stella, Rafael; Freddy Yeo, Kuok San; Walftor, Dumin; Surisa, Phornvillay; Yap, Jun Wah; Najaa Batrisyia, Abdullah Zakaria; Lai, Lee San (Elsevier Inc., 2025)
Pyricularia oryzae, the causal agent of rice blast disease, poses a significant threat to rice production. Limited information exists regarding the genetic diversity of Avr genes and the resistance profile of Sarawak rice against P. oryzae isolates in Malaysia. This study aimed to investigate the sequence variation of the AvrPi-54 gene in P. oryzae isolates from Sarawak rice, in comparison with sequences available in the National Centre for Biotechnology Information (NCBI) database. A total of 20 P. oryzae isolates were analyzed together with 98 AvrPi-54 gene sequences from NCBI. Nine distinct haplotypes were identified, including six novel haplotypes. The AvrPi-54 gene was found to be under positive selection pressure. Notably, Sarawak rice exhibited varying levels of susceptibility to P. oryzae isolates carrying the H1 haplotype. Understanding the genetic diversity of AvrPi-54 together with other Avr genes is crucial for developing effective strategies to manage P. oryzae in Sarawak, Malaysia.